Early Language Learning in Europe: a multinational, longitudinal study - Szpotovicz, Magda (Array, 2009)
This paper presents an outline of the research framework for a longitudinal, comparative study of early language learning (ELL) across seven European country contexts (Croatia, England, Italy, Netherlands, Poland, Spain and Sweden). In addition, two strands of evidence from the initial one-year scoping study are explored here, providing an early account of emerging findings and offering an indication of outcomes to be reported in the further three years of the research. Given the European priority for introducing early foreign languages in schools, there is now an urgent need for both qualitative and quantitative evidence on the precise nature and outcomes of ELL, as highlighted by the recent European Commission Report ‘ Languages for the children of Europe’ (Edelenbos et al., 2006). This research aims to provide a much-needed body of data of sufficient scale to offer the kind of validity that previous studies have been unable to achieve, with the potential strategically to inform both future policy and practice.